Exploration status for oxide and sulphide zinc ores at Skorpion Zinc Mine, Namibia - Sitoka, Stefanus (Rhodes University, Faculty of Science, Department of Geology, 2015)
The thesis is inspired by recent interests in oxide zinc ores caused by new developments in the technology of hydrometallurgy. The improved techniques turned the non-sulphide zinc ores in to attractive exploration targets due to a number of advantages such as low metal recovery costs and favorable environmental aspects such as the obvious absence of sulfur (Large, 2001). Historically extraction of zinc metal from oxide ores was not possible until recently. The metallurgical complexity resulted in a lack of interest and hence some economic oxide zinc ores might have been missed by conventional exploration techniques. The study presents a review of exploration status at Skorpion mine based on different exploration techniques and their application to sulphide and oxide zinc ore exploration. The challenge facing the mineral exploration industry today is the inability to detect mineral deposits under cover. Therefore a key to successful exploration program lies in the selection of the right exploration technique. Important parameters that should be highlighted in the exploration methodology are the geological situation of an area, equipment applicability and effectiveness, survey limitation, equipment mobilization and the safety aspects involved. The aim of this thesis is to provide a general guideline for sulphide and non-sulphide zinc ore exploration on the Skorpion area and other similar geological environments. Geochemical surveys appears to be more complimentary in exploration of non-sulphide zinc exploration. Although geochemical techniques are preferred, it is equally important to choose the right soil horizon. Furthermore, sample media may mean the difference between success and failure in geochemical exploration of non-sulphide zinc mineralization, due to high mobility of zinc in the surficial environment. On cost comparison, surface geochemical surveys programs are more cost effective except for litho-geochemical sampling which are commonly carried out through subsurface drilling. Geophysical techniques have limited application in exploration of non-sulphide zinc mineralization due to a lack of major physical properties (e.g., magnetic and electrical properties) in non-sulphides unlike their sulphide counterparts. However geophysical methods are commendable in delineating massive and disseminated sulphides mainly if they are associated with major Fe minerals (pyrrhotite or magnetite). In addition, geophysical techniques may be effective in mapping of subsurface primary and secondary structures such as basin faults which might have acted as pathways for metal-rich fluids. Terms non-sulphide and oxide zinc mineralization are used interchangeably throughout the thesis. Recommendations on regional and local target generation are presented in the thesis to give some basic guide lines on target generation strategies. The most important conclusion reached in this study is that, success in exploration for non-sulphide or sulphide zinc mineralization might be enhanced through the integrated exploration methodology.
Keywords: Scorpion Zinc Mine (Namibia); Zinc ores; Oxide minerals; Sulfide minerals; Zinc mines and mining -- Namibia; Prospecting -- Namibia